Analysis of Teachers' Efforts to Improve Elementary School Students' Reading Comprehension Ability in Indonesian Language Learning - Noesti Ramadhani; Safrizal Safrizal; Husnani Husnani (Universitas Sang Bumi Ruwa Jurai, 2023)
The large number of students who experience difficulties in understanding reading texts reflects challenges in education that require more attention to the development of reading comprehension skills among students. Therefore, the aim of this research is to describe teachers' efforts to Improve Elementary School Students' Reading Comprehension Ability in Indonesian Language Learning. The research method used is a qualitative method with the type of research used is a case study. The informants in this research were 2 grade 5 (fifth) elementary school teachers and grade 5 (fifth) elementary school students who were selected based on purposive sampling technique. Data collection techniques were carried out using interviews, observation and documentation. The data obtained was then analyzed using the Miles and Huberman model, namely with the stages of data reduction, data presentation, and drawing conclusion. To ensure the validity of the data, this research uses data triangulation techniques. The study's findings indicate that teachers can assist students in grade 5 in primary school improve their reading comprehension skills by using books to teach additional literacy within the first 10 minutes before learning begins.